Pharmacological activation of mitochondrial BK(Ca) channels protects isolated cardiomyocytes against simulated reperfusion-induced injury - Borchert, Gudrun H; Hlaváčková, Markéta; Kolář, František (Experimental biology and medicine (Maywood, N.J.), 2013)
The aim of this study was to find out whether opening of mitochondrial large-conductance Ca(2+)-activated potassium channels (BK(Ca)) protects cardiomyocytes against injury caused by simulated ischemia and reperfusion. This study also aimed to determine whether the protective mechanism involves signaling by reactive oxygen species (ROS) and phosphatidylinositol-3-kinase (PI3K). We used isolated ventricular myocytes, which are believed to contain no functional BK(Ca) channels in the sarcolemma. Cells were isolated from the left ventricles of adult male Wistar rats and subjected to 25-min metabolic inhibition with NaCN and 2-deoxyglucose followed by 30-min re-energization. NS11021 (0.1 μmol/L), a novel BK(Ca) channel opener, or hydrogen peroxide (2 μmol/L) added at re-energization, increased cell survival (the number of rod-shaped cells) and markedly reduced the release of lactate dehydrogenase (LDH). These cytoprotective effects of NS11021 were completely abolished by paxilline, a BK(Ca) inhibitor, or tempol, an antioxidant, but not by wortmannin, an inhibitor of PI3K. NS11021 slightly but significantly increased the fluorescence signal in 2'7'-dichlorodihydrofluorescein diacetate (DCF-DA)-loaded myocytes, indicating an increased ROS formation. The NS11021-induced ROS formation was abolished by paxilline or tempol. NS13558 (0.1 μmol/L), an inactive structural analogue of NS11021, affected neither cell survival/LDH release nor DCF-DA fluorescence. These results suggest that pharmacological activation of mitochondrial BK(Ca) channels effectively protects isolated cardiomyocytes against injury associated with simulated reperfusion. The mechanism for this form of protection requires ROS signaling, but not the activation of the PI3K pathway.
Keywords: L-laktátdehydrogenasa; Large-Conductance Calcium-Activated Potassium Channel alpha Subunits; reperfuzní poškození myokardu; viabilita buněk; Cardiovascular Agents; Male; vápníkem aktivované draslíkové kanály s vysokou vodivostí - alfa-podjednotky; Rats, Wistar; Thiourea; kardiovaskulární látky; Myocardial Reperfusion Injury; Cell Survival; peroxid vodíku; mužské pohlaví; potkani Wistar; thiomočovina; Hydrogen Peroxide; Tetrazoles; krysa rodu Rattus; kardiomyocyty; Animals; zvířata; Rats; tetrazoly; Myocytes, Cardiac; L-Lactate Dehydrogenase